Does Playing Tennis with a Low-Compression Ball Effect Psychophysiological Responses and Match Characteristics in Recreational Adult Players? - Kilit, Bulent; Arslan, Ersan; Soylu, Yusuf; Lane, Andrew M. (Sports (Basel), 2024)
This study aimed to compare the effects of playing tennis using low-compression balls (Lc-Balls) and standard balls (St-Balls) on psychophysiological responses and match characteristics among recreational adult tennis players. Participants (N = 24; age: 20.5 ± 1.3 years) were randomly matched to play two singles matches over three sets: one match was played with a Lc-Ball and one match was played with a St-Ball, resulting in twenty-four matches. Heart-rate responses and match characteristics were assessed during each match. Post-match measures included retrospective assessments of perceived exertion, ratings of enjoyment towards physical activity, and ratings of mental effort and mood. Results showed higher psychophysiological responses and more intensive play during the game when playing with the Lc-Ball (p ≤ 0.05, d values ranging from 0.24 to 1.93 [small to very large effect]). Further, playing with a Lc-Ball related to reporting a lower rating of perceived exertion (p = 0.00, d = 0.90 [moderate effect]) and greater physical enjoyment (p = 0.00, d = 1.73 [large effect]). Playing with the St-Ball was associated with higher unpleasant mood responses including depression, tension, anger, and fatigue. In conclusion, the results suggest that using the Lc-Ball may lead to better match performance with higher enjoyment in the tennis match-play in recreational adult tennis players.